What does heat tell a mosquito? Characterization of the orientation behaviour of Aedes aegypti towards heat sources. (July 2017) - Zermoglio, Paula F.; Robuchon, Eddy; Leonardi, María Soledad; Chandre, Fabrice; Lazzari, Claudio R.
Graphical abstract: Highlights: Female A. aegypti orient to host-temperature sources in the absence of other cues. Males do not respond to host-temperature heat sources. Females orient to closer host-temperature sources. Females do not discriminate heat sources according to their size. Females do not us IR radiation to orient towards heat sources. Abstract: The use of heat as a cue for the orientation of haematophagous insects towards hot-blooded hosts has been acknowledged for many decades. In mosquitoes, thermoreception has been studied at the molecular, physiological and behavioural levels, and the response to heat has been evaluated in multimodal contexts. However, a direct characterization of how these insects evaluate thermal sources is still lacking. In this study we characterize Aedes aegypti thermal orientation using a simple dual choice paradigm, providing direct evidence on how different attributes of heat sources affect their choice. We found that female mosquitoes, but not males, are able to discriminate among heat sources that are at ambient, host-range and deleterious temperatures when no other stimuli are present, eliciting a positive response towards host-range and an avoidance response towards deleterious temperatures. We also tested the preference of females according to the size and position of the sources. We found that females do not discriminate between heat sources of different sizes, but actively orientate towards closer sources at host temperature. Furthermore, we show that females cannot use IR radiation as an orientation cue. Orientation towards a host involves the integration of cues of different nature in distinct phases of the orientation. Although such integration might be decisive for successful encounter of the host, we show that heat alone is sufficient to elicit orientation behaviour. We discuss the performance of mosquitoes' thermal behaviour compared to other blood-sucking insects.